2023
DOI: 10.3389/fonc.2023.1122294
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm phase II clinical trial of anlotinib combined with chemotherapy for the treatment of metastatic triple-negative breast cancer

Abstract: BackgroundAnlotinib is a novel oral small-molecule tyrosine kinase inhibitor (TKI), which can inhibit angiogenesis. The purpose of this study was to evaluate the efficacy and safety of anlotinib combined with chemotherapy in patients with metastatic triple-negative breast cancer (TNBC).MethodsThis phase II clinical trial included 40 patients with metastatic TNBC who had previously received anthracycline and/or taxane treatment. All patients received anlotinib combined with chemotherapy. The primary endpoint wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A phase Ib clinical study showed that a combination of a tyrosine kinase inhibitor (anlotinib) and an immune checkpoint inhibitor (anti-PD-L1 antibody) showed promising efficacy with a good safety profile provides a chemotherapy-free treatment for TNBC patients 9 . In another phase II clinical trial, the combination of this tyrosine kinase inhibitor and chemotherapy also showed a certain efficacy and acceptable safety profile to treat metastatic triple-negative breast cancer patients 10 . A tyrosine kinase, SRC overexpression is frequently found in TNBC patients and associated with tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…A phase Ib clinical study showed that a combination of a tyrosine kinase inhibitor (anlotinib) and an immune checkpoint inhibitor (anti-PD-L1 antibody) showed promising efficacy with a good safety profile provides a chemotherapy-free treatment for TNBC patients 9 . In another phase II clinical trial, the combination of this tyrosine kinase inhibitor and chemotherapy also showed a certain efficacy and acceptable safety profile to treat metastatic triple-negative breast cancer patients 10 . A tyrosine kinase, SRC overexpression is frequently found in TNBC patients and associated with tumor malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…This combination not only demonstrated favorable efficacy but also maintained a manageable safety profile ( 107 ). Another Phase II clinical trial combining Anlotinib with standard chemotherapy for metastatic TNBC demonstrated therapeutic benefits with manageable safety ( 108 ).…”
Section: Current Therapeutic Applications Of the Jak2/stat3 Signaling...mentioning
confidence: 99%